Biphasic Oxidation of Oxy-Hemoglobin in Bloodstains - Bremmer, Rolf H. (Public Library of Science, 2011)
BACKGROUND: In forensic science, age determination of bloodstains can be crucial in reconstructing crimes. Upon exiting the body, bloodstains transit from bright red to dark brown, which is attributed to oxidation of oxy-hemoglobin (HbO(2)) to met-hemoglobin (met-Hb) and hemichrome (HC). The fractions of HbO(2), met-Hb and HC in a bloodstain can be used for age determination of bloodstains. In this study, we further analyze the conversion of HbO(2) to met-Hb and HC, and determine the effect of temperature and humidity on the conversion rates. METHODOLOGY: The fractions of HbO(2), met-Hb and HC in a bloodstain, as determined by quantitative analysis of optical reflectance spectra (450–800 nm), were measured as function of age, temperature and humidity. Additionally, Optical Coherence Tomography around 1300 nm was used to confirm quantitative spectral analysis approach. CONCLUSIONS: The oxidation rate of HbO(2) in bloodstains is biphasic. At first, the oxidation of HbO(2) is rapid, but slows down after a few hours. These oxidation rates are strongly temperature dependent. However, the oxidation of HbO(2) seems to be independent of humidity, whereas the transition of met-Hb into HC strongly depends on humidity. Knowledge of these decay rates is indispensable for translating laboratory results into forensic practice, and to enable bloodstain age determination on the crime scene.